2022
DOI: 10.1039/d1mh01612a
|View full text |Cite
|
Sign up to set email alerts
|

Local chemical fluctuation mediated ultra-sluggish martensitic transformation in high-entropy intermetallics

Abstract: Superelasticity associated with the martensitic transformation has found a broad range of engineering applications such as low-temperature devices in aerospace industry. Nevertheless, the narrow working temperature range and strong temperature...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 63 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Since the first HESMA was reported by Firstov et al [13], up to now, most reported HESMAs have been tested in compression [14,15,17,18]. With our knowledge, the present Ti 30 Ni 30 Fe 10 Hf 10 Nb 20 EHEA was firstly reported to possess high strength and superelasticity in tension, which exhibits tensile strength as high as 1409 MPa and superelasticity as large as 3.1%.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Since the first HESMA was reported by Firstov et al [13], up to now, most reported HESMAs have been tested in compression [14,15,17,18]. With our knowledge, the present Ti 30 Ni 30 Fe 10 Hf 10 Nb 20 EHEA was firstly reported to possess high strength and superelasticity in tension, which exhibits tensile strength as high as 1409 MPa and superelasticity as large as 3.1%.…”
Section: Resultsmentioning
confidence: 77%
“…It is attributed to high elastic modulus and high yield strength, which are originated from the core effects of HEAs, such as high entropy, sluggish diffusion and lattice distortion, etc. Subsequently, SME at an ultrahigh temperature, large elasticity at an elevated temperature and superelasticity at a low temperature have also been reported in the Ni-Pd-Ti-Zr-Hf [14], Ti-Hf-Zr-Cu-Ni [15,16] and Ti-Zr-Hf-Cu-Ni-Co [17] alloy systems, respectively. The interaction of multicomponents effectively suppresses the plastic deformation during the process of martensitic transformation, improving the performance of SME [18].…”
Section: Introductionmentioning
confidence: 89%
“…To date, a great deal of work has been carried out on the L1 2 -type multicomponent precipitates and many encouraging achievements have been obtained [1][2][3][5][6][7]. It has been demonstrated that the precipitates precipitated from the matrix of multi-principal elements alloys (MPEAs) are rich in variable components.…”
Section: Introductionmentioning
confidence: 99%